The NORMATIVE STUDY OF CENTRAL MARINE DEVELOPMENT POLICY AND INTEGRATED FISHERIES IN SMALL ISLANDS AND BORDER AREA BASED ON KKP REGULATION NUMBER 48/2015 - Kennedy, Posma Sariguna Johnson (Fundamental Management Journal, 2018)
To realize the Vision and Mission of the Ministry of Maritime Affairs and Fisheries (KKP) in the form of sovereignty, sustainability and welfare, there is the concern to build small islands and border areas with the Integrated Marine and Fisheries Center (SKPT) program in an integrated and comprehensive manner. This study aims to look at the norms of what is best for building small islands in the border region in terms of the development of fisheries centers. The target is to meet the nutritional needs of local communities, support national food security and generate state revenues through export activities as well as accelerate local economic growth. Keywords: Normative study, Border area, Development policy, Small islands, Integrated Marine and Fishery Center.